Reproductive outcomes of pregnancy after breast cancer: an updated systematic review and meta-analysis - Song, Qingya; Mei, Heting; Lu, Wenping; Zhang, Weijia; Liu, Jiaxin; Wang, Xiyue; Zhuo, Zhili; Chang, Lei (Frontiers in Oncology, 2025)
BackgroundReproductive outcomes following pregnancy in premenopausal women with breast cancer (BC) remain contentious, and few meta-analyses have adequately addressed these questions. This systematic review and meta-analysis aimed to provide the most up-to-date and comprehensive evidence on the subject.MethodsTen electronic databases were searched in September 2024 using the terms “Breast Neoplasms” AND “Pregnancy OR Fertilization OR Parturition OR Fertility OR Obstetrics”. Key inclusion criteria focused on reproductive outcomes in premenopausal women with BC compared to healthy populations. Primary outcomes included pregnancy outcomes, obstetrical outcomes, fetal outcomes, and pregnancy complications. The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the Meta - analysis of Observational Studies in Epidemiology (MOOSE) statement. Depending on the study type, dichotomous variables were analyzed using relative risk, odds ratio, hazard ratio, standardized birth ratio, and 95% confidence interval. To preserve the accuracy of findings, original effect measures were used, while other studies were addressed in the systematic review.ResultsOut of 35,324 records identified, 26 studies met the inclusion criteria. The meta-analysis indicated that women with breast cancer had lower pregnancy prevalence, lower completed pregnancy rate, lower childbirth rate, lower birth trauma rate, and higher rates of cesarean delivery and preterm birth compared to healthy controls. Offspring of women with breast cancer had higher risks of very low birth weight, low birth weight, fetal abnormalities, and a lower live birth rate. The systematic review further showed increased risks of intrapartum hemorrhage, induced delivery, spontaneous delivery, failed induction of labor, prolonged labor, fetal stress, and delivery-related complications in this group, along with a lower rate of full-term delivery and reduced incidence of gestational hypertension.ConclusionsPregnancy outcomes after breast cancer are often unsatisfactory. Patients and clinicians should approach pregnancy planning with care, ensuring thorough assessment and appropriate testing throughout the process.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024499971.